Comparative Effects of Compound Enzyme and Antibiotics on Growth Performance, Nutrient Digestibility, Blood Biochemical Index, and Intestinal Health in Weaned Pigs - Li, Zhiqing; Tang, Lizi; Liu, Nian; Zhang, Fan; Liu, Xiang; Jiang, Qian; Chen, Jiashun; Ma, Xiaokang (Frontiers in Microbiology, 2021)
This experiment aims to explore the effects of compound enzyme preparation substituting chlortetracycline on growth performance, serum immune markers, and antioxidant capacity and intestinal health in weaned piglets. A total of twenty-four 28-day-old “Duroc × Landrace × Yorkshire” weaned piglets with an average initial weight of 7.25 ± 0.25 kg were randomly divided into three groups according to their body weight, with eight replicates in each group and one pig in each replicate. The three dietary treatments were basal diet (CON), basal diet + 1,000 mg/kg compound enzyme preparation (cellulase 4,000 IU/g, α-amylase 1,000 IU/g, β-glucanase 150 IU/g, and neutral protease 3,000 IU/g, CE), and basal diet + 75 mg/kg chlortetracycline (CTC). The animal experiment lasted for 28 days and was divided into two stages: the early stage (0–14 days) and the late stage (15–28 days). The results showed that (1) compared with the CON, the CE and CTC significantly increased the ADG of weaned piglets during the early and whole period of experiment (p < 0.05), decreased the F:G in the whole experiment period (p < 0.05), and diarrhea rate in the early stage (p < 0.01). (2) Compared with the CON, the apparent total tract digestibility of ADF and NDF was significantly increased in pigs fed the CE diet in the early and late stages of experiment (p < 0.05) with no significant difference compared with the CTC. (3) Compared with the CON, the concentrations of serum IgA and SOD in weaned piglets were significantly increased in the CE group in the early stage of the experiment (p < 0.05). (4) Compared with the CON group, the acetic acid, propionic acid, and total VFA contents in cecum and colon segments were elevated in the CE group (p < 0.05) with no significant difference compared with the CTC. (5) Compared with the CON group, the villus height of duodenum and jejunum and the ratio of villus height to recess depth of ileum were increased in the CE and CTC group (p < 0.05). (6) Compared with the CON group, the abundance of Lactobacillus significantly increased (p < 0.01) while the abundance of Escherichia coli decreased in the CE group and CTC group (p < 0.01). In conclusion, CE preparation instead of CTC can significantly improve the nutrient digestibility, the immunity, antioxidant capacity, and intestinal health of pigs, which may contribute to the improved growth performance of piglets.